Modification of Media for Banana In Vitro Propagation with Foliar Fertilizer and Coconut Water in cv. Rajabulu - Siti Mardhikasari; Ahmad Yunus; Samanhudi Samanhudi (Universitas Sebelas Maret, 2020)
The use of foliar fertilizers and coconut water is potential; foliar fertilizer is the alternative medium and coconut water is the plant growth regulator (PGR) in the banana tissue culture. This study aimed to examine the ability of foliar fertilizer to substitute Murashige and Skoog (MS) media and coconut water as the main source of cytokine. There are two factors in this research. The first factor is the media, which consist of three levels, i.e. fully MS, ½ MS + ½ foliar fertilizer and fully foliar fertilizer. The second factor is the coconut water with four levels of concentration i.e. 50, 100, 150 and 200 ml l-1. The results show that fully formulated foliar fertilizer had not been able to substitute or even compete with a fully MS media, but conversely foliar fertilizer was used to substitute ½ MS media. This can be seen from the parameters of shoot length, leaf length, root number and root length with the highest yield that was found in MS media (8.7, 4.66, 3.33 and 3.23 cm). The 50-100 ml l-1 concentrations of coconut water showed the best results by giving a significant effect on the number of roots and root length. The acclimatization of plantlets in this study was nearly 100%, indicated by the formation of a complete organ.